Analisa Rentang Waktu Pembukaan Valve pada Sistem Automatic Draining di Clean Oil Tank - Ahmad Mahfud (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Clean oil tank is one of the equipment at the station clarification shaped cylindrical tank with a cone at the bottom. The function of clean oil tanks is to reduce the amount of dirt that is still contained in the oil depositionly. At the bottom there is a clean oil tank valve for the disposal of sewage sludge. The use of pneumatic valve system with loading time can be set on a time delay relay. The research method is done by testing samples at the laboratory scale by depositing the sample ex CST with temperature 85oC, then analyzed manure content reduction. Decreased levels of these impurities is assumed as the level of impurities that can settle to the bottom clean oil tank. Based on the data that has been obtained, to analyze the test results and the data is then processed using a simple mathematical model in order to know the optimal timing of valve setting autodrain on clean oil tank 1 and 2 during processing.